Membangun Kesehatan Dari Dalam Dengan Menu Sehat Berprotein Tinggi - Kumawati Rofidah; Nira Putriana; Alifah Gita Cahyani Roqimah; Liss Dyah Dewi Arini (Jurnal Ilmu Kesehatan dan Gizi, 2024)
The purpose of this study is to understand the importance of building health through a high-protein healthy menu. This research employs a qualitative descriptive approach to collect data through observation and literature review methods. The results of the study indicate that by planning menus, choosing food wisely, cooking at home, and paying attention to balanced portion sizes, we can practically implement a high-protein diet in daily life to support optimal health.